Breast myofibroblastoma: Report of two cases with literature review - Bouhani, Malek; Adouni, Olfa; Marghli, İkram and Chemlali, Molka and Chargui, Riadh and Rahal, Khaled (Journal of Surgery and Medicine, 2020)
Myofibroblastoma (MFB) is a rare mesenchymal benign tumor that arises from the stromal structures of the breast tissue. It occurs in the elderly without sex predilection. Its clinical and radiological presentations are aspecific, thus MFB may be confounded with other malignant and benign breast lesions. However, the main histological characteristic of MFB is the presence of spindle cells in a collagenous background. In immunohistochemistry, MFB is positive for vimentin and CD34 with a noticeable low mitotic activity. Surgical excision remains the treatment cornerstone, with excellent outcomes. We retrospectively reviewed the records of all the patients who underwent surgery of breast from 01 January 2012 to 31 December 2018. We found two cases of breast myofibroblastoma. The first was a young woman aged 17 years, and the second was a male aged 87 years. The main symptom was a palpable breast lump in both patients. The radiological work up concluded to a benign lump in the young woman, and a suspicious breast lump in the man, to whom we performed a core biopsy. Histology staining showed the features of MFB. The woman underwent a lumpectomy, and the man underwent a mastectomy. Final histological staining showed spindle cells with a collagen matrix. The cells were positive for CD34, vimentin, and actin. Those features were compatible with the diagnosis of breast MFB. The aim of this report was to describe the clinical, radiological and histological features of breast MFB.